Incorporating Adverse Childhood Experiences (ACE) Training in Baccalaureate Nursing Curriculum. - Cross, Cynthia R.; Morehead, Monica M.; McCaulley, Heidi B. (South Carolina Nurse, 2024)
In baccalaureate nursing education, comprehensive health assessments are fundamental in the care of patients, families, and communities. Comprehensive health assessments lead to further examination of the social determinants of health for the client as related to the overall outcomes of a client's health. Social determinants of health are directly related to adverse childhood experiences. Adverse childhood experiences spotlight specific events that are related to social determinants of health. Being able to recognize a client's physical and mental health status as they relate to adverse childhood experiences will help produce better overall health assessment outcomes for individuals and populations. It is recommended to incorporate adverse childhood experiences or ACE training into baccalaureate nursing education.